Feasibility of a bilateral 4000–6000 Hz notch as a phenotype for genetic association analysis. (3rd October 2015) - Phillips, Susan L.; Richter, Scott J.; Teglas, Sandra L.; Bhatt, Ishan S.; Morehouse, Robin C.; Hauser, Elizabeth R.; Henrich, Vincent C.
Abstract: Objective: Noise-induced hearing loss (NIHL) is a worldwide health problem and a growing concern among young people. Although some people appear to be more susceptible to NIHL, genetic association studies lack a specific phenotype. We tested the feasibility of a bilateral 4000–6000 Hz audiometric notch as a phenotype for identifying genetic contributions to hearing loss in young adults. Design: A case-control-control study was conducted to examine selected SNPs in 52 genes previously associated with hearing loss and/or expressed in the cochlea. A notch was defined as a minimum of a 15-dB drop at 4000–6000 Hz from the previous best threshold with a 5-dB 'recovery' at 8000 Hz. Study sample: Participants were 252 individuals of European descent taken from a population of 640 young adults who are students of classical music. Participants were grouped as No-notch (NN), Unilateral Notch (UN), or Bilateral Notch (BN). Results: The strongest evidence of a genetic association with the 4000–6000 Hz notch was a nonsynonymous SNP variant in the ESRR– gene (rs61742642:C> T, P386S). Carriers of the minor allele accounted for 26% of all bilateral losses. Conclusion: This study indicates that the 4000–6000 Hz bilateral notch is a feasible phenotype for identifying genetic susceptibility to hearing loss.